2003
DOI: 10.1109/tasc.2003.812067
|View full text |Cite
|
Sign up to set email alerts
|

Improving the critical current density in Bi-2223 wires via a reduction of the secondary phase content

Abstract: Index Terms-Bi-2223 tape, critical current density, high temperature superconductor, microstructure analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Implications for are examined. For the first time, width-normalized values that are comparable to commercial Ag-Bi-2223 multi-filamentary composite (MFC) wire [10] were obtained.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Implications for are examined. For the first time, width-normalized values that are comparable to commercial Ag-Bi-2223 multi-filamentary composite (MFC) wire [10] were obtained.…”
Section: Introductionmentioning
confidence: 89%
“…Following conversion, the water supply is turned off, starting a drying time of 3 min, prior to cooling. Excluding the drying time, annealing durations corresponding to growth rates of [5][6][7][8][9][10][11][12] were found to produce complete conversion into YBCO for thickness values ranging from 0.2-2 . Electrical resistivity values at room temperature were in the range 200-300 .…”
Section: Fast Conversion Processmentioning
confidence: 99%
“…From the results of figures 3 and 6, it is considered that the higher density of 2212 intergrowths was contained in the (Bi, Pb)2223 phase formed in the early stage, and the density gradually decreased as the (Bi, Pb)2223 phase transformation proceeded. Furthermore, in [35], TEM showed that the higher density of 2212 intergrowths was contained in the (Bi, Pb)2223 phase that was furthest from the liquid phase. Based on this consideration, the model of 2212 intergrowth formation in the (Bi, Pb)2223 phase is suggested as shown in figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Although today's (Bi, Pb)2223/Ag tapes have large transport current densities, there remains plenty of room for improvement [1].…”
Section: Introductionmentioning
confidence: 99%